Desain dan kontrol robot pemandu pengunjung otonom di lingkungan rumah sakit (Robot Viguro): Desain dan kontrol robot pemandu pengunjung otonom di lingkungan rumah sakit (Robot Viguro) - Agus Siswoyo; Rodik Wajyu Indrawan (Politeknik Aceh, 2023)
In recent years, the development of autonomous robots for healthcare applications has gained significant interest. This paper presents the design and development of an autonomous robot tailored for guiding visitors in healthcare facilities, aiming to enhance their experience and provide efficient navigation. Equipped with huskylens cameras, proximity sensors, and other sensors, the robot perceives its environment and detects obstacles. A robust navigation system incorporates mapping and localization algorithms, enabling real-time mapping and accurate positioning. Through a user-friendly interface, visitors input their destination, and the robot plans an optimal path considering distance, obstacles, and congestion. It adapts to dynamic changes like moving objects or crowded areas for safe and efficient navigation. The development process involved iterative design, prototyping, and testing, incorporating feedback from staff and visitors for improved functionality and user experience. Preliminary pilot test results demonstrate the effectiveness of the autonomous guiding robot, providing accurate navigation and enhancing visitor satisfaction. This research contributes to advancing autonomous robotics in healthcare by addressing the need for visitor guidance, improving efficiency, potentially reducing staff workload, and enhancing overall experiences for patients and visitors.